PENERAPAN MODEL GROUP INVESTIGATION BERBANTUAN MEDIA PEMBELAJARAN POSTER SEBAGAI SOLUSI DALAM PEMBELAJARAN MATEMATIKA PADA SISWA SEKOLAH DASAR - Anugrawati, Nasrun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is the low learning outcomes of students, especially in class V of SD Inpres Malakaya, Gowa Regency. This study aims to improve student learning outcomes by using the Group Investigation (GI) type cooperative model assisted by poster learning media in class V of SD Inpres Malakaya, Gowa Regency. This study uses the Classroom Action Research (CAR) method. The location of this research was carried out at SD Inpres Malakaya, Gowa Regency. The subjects in this study were students of class V of SD Inpres Malakaya, Gowa Regency with a total of 25 students in the 2022/2023 academic year. The research procedure includes planning, implementing actions, observation and reflection. The data obtained from the research results were analyzed using descriptive statistics used to describe student learning outcomes using the Group Investigation (GI) type cooperative model assisted by poster learning media. The results achieved in this study are: (1) There was an increase in student learning activities and teacher activities in each cycle. (2) In the first cycle, the average value of learning outcomes for class V students of SD Inpres Malakaya, Gowa Regency was 64, while in the second cycle, the average value of learning outcomes was higher, reaching 83.2. The mathematics learning completion of class V students of SD Inpres Malakaya, Gowa Regency also increased. In cycle I, there were 12 students or 48% who achieved learning completion, while in cycle II, 24 students or 96% achieved learning completion and classical learning completion was achieved. This means that learning completion in cycle II was achieved classically because the number of students who completed it reached 80%. Based on the results of the study above, it can be concluded that the results of learning mathematics through the cooperative model of the Group Investigation (GI) type assisted by poster learning media in class V of SD Inpres Malakaya, Gowa Regency increased.